Ableitungsregeln Zusammenfassung

Lesedauer: 1 min | Vorlesen | Autor: Dr. Volkmar Naumburger

Konstante: \((k \cdot f(x))' = k \cdot f'\left( x \right)\)

Summenregel: \((u + v)' = u' + v'\)

Produktregel: \((u \cdot v)' = u' \cdot v + u \cdot v'\)

Quotientenregel: \({\left( {\frac{u}{v} } \right)^\prime } = \frac{ {u' \cdot v - u \cdot v'} }{ { {v^2} } }\)

Kettenregel: \(\frac{ {du\left( v \right)} }{ {dx} } = \frac{ {du} }{ {dv} } \cdot \frac{ {dv} }{ {dx} }\)

Parameterregel: \(\frac{ {dy(t)} }{ {dx(t)} } = \frac{ {dy} }{ {dt} } \cdot {\left({\frac{ {dx} }{ {dt} } } \right)^{ - 1} }\)

  Hinweis senden